Research on 5G private network service solutions - Zhang Qing; Feng Yi; Qin Xiaofei; Cao Kang (Dianzi Jishu Yingyong, 2022)
As one of the important engines to promote the digital transformation of the society, 5G private networks have been applied to industries such as electric power, mining, education, and medical care. After analyzing the rich and diverse service requirements of current industry customers for 5G private networks, firstly it is proposed that the core service capabilities that the 5G private network can provide customers in four aspects: native capability, data capability, collaboration capability and operational capability. Secondly, it is further discussed that scenario-based private network services such as low latency, large bandwidth, high reliability, strong security and flexible networking can be formed through effective organization of core service capabilities. Finally, it analyzes how to use private network services to form industry private network solutions, taking mining, electric power, port and other industry requirements as examples.